O sentido e alcance do princípio do planejamento no direito urbanístico - Cordeiro, Alexandre (2007)
Innovative experiences in governance and local authority have given the debate on urban planning and intervention renewed topicality, bringing to light the recurring unease to assert the meaning and extent of the principle of urban planning as a postulate grounding the implementation of related policies. From a broader perspective, these concerns translate into the need to ensure the full normative effectiveness of the principle-based rule, to the point where it enables to objectively outline the boundaries within which the posit of development bespeaks conditions for social equality, rational conservation of natural resources, good level of welfare, respect of sociocultural identities. That necessarily implies addressing the dimension of values associated with urban life as determinants of development policies. Not only, however. As a two-way road, it also implies determining whether the factual action of the players in charge actually ensures the observance of said values, in many aspects legally codified by normative contents derived from principle-based posits that provide guidance for the exercise of the administrative function as a specific legal activity. To this end, said view should not be disqualified by merely claiming it to resemble a utopian notion. On the contrary, as the present study intends to demonstrate, the legal contents of planning as a principle not only should guide all administrative action undertaken on the grounds of legal competences defining public land-ordering policies but will also provide, to a large extent, legal density for the technical elements that best attest to the pursuance of said propositions